Vibrio cholerae O1 El Tor A1552 encodes two functional ornithine lipid synthases and induces ornithine lipid formation under low phosphate and under low salinity growth conditions. - Miguel Ángel Vences-Guzmán; Roberto Jhonatan Olea-Ozuna; Raquel Martínez-Méndez; Wendy Itzel Escobedo-Hinojosa; Marlene Castro-Santillán; Ziqiang Guan; David Zamorano-Sánchez; Christian Sohlenkamp (PLoS ONE)
Ornithine lipids (OLs) are phosphorus-free membrane lipids that can be formed by a wide range of bacteria. The presence of OLs is frequently related to the resistance to abiotic stress conditions, and their synthesis is often induced as part of various stress responses. Two different pathways for synthesizing OLs are currently known: the OlsBA pathway, first described in Sinorhizobium meliloti, and the OlsF pathway, first described in Serratia proteamaculans. We identified in the genome of Vibrio cholerae O1 El Tor A1552 two genes encoding OlsF homologs, VC0489 is located on chromosome 1, whereas VCA0646 is located on chromosome 2. Both synthases, when expressed in Escherichia coli, caused the synthesis of OLs. Single mutants deficient in each of the OL synthases, double mutants deficient in both OL synthases, and mutants deficient in the transcriptional regulator PhoB were constructed and characterized. We corroborated that VC0489 is solely responsible for the synthesis of OLs under phosphate limitation. The deletion of VC0489 reduced the growth velocity compared to the wildtype under phosphate-limiting conditions but not under phosphate-replete conditions. The expression of VCA0646 is favored under low salt growth conditions, and its deletion abrogates OL synthesis at low salinities. The absence of VCA0646 and, therefore, the lack of OLs under low salt conditions makes the respective mutant more susceptible to polymyxin than OL-forming strains under these conditions. None of the mutants was affected in biofilm formation, swimming, or virulence assays using standardized survival assays with Caenorhabditis elegans or Galleria mellonella. Here, we describe two functional OL synthases present in a single bacterium for the first time, and we show evidence that OLs have an important function during the V. cholerae lifecycle.